2D shape optimization using genetic algorithm - Kita, Eisuke (Computer Assisted Methods in Engineering and Science, 1998)
This paper presents an optimal design method of continuum structures by genetic algorithm. Profiles of the objects under consideration arc represcnted by the spline functions and then, the chromosomes for the profiles are defined by the coordinates of the control points of the functions and the material code of the structures. The profiles and the material code are optimized by the genetic operations in order to determine the object satisfying the design objectives. The minimum weight design of the plate is considered as a typical example. The present method is applied to the problem in which the profile and the material of the objects are unknown.